Understanding the molecular pathogenesis of HIV-associated Burkitt Lymphoma – the impact of HIV-1 protein Tat on lymphoma driver genes - Alves, de Souza Rios Leonardo (Department of Pathology, 2021)
Burkitt Lymphoma (BL) is a B cell non-Hodgkin lymphoma that occurs as three distinct subtypes, namely: endemic, sporadic, and immunodeficiency/HIV-associated. This cancer represents a frequent cause of mortality among HIV+ people in Southern Africa which has the highest incidence of HIV/AIDS worldwide. Recent reports associate a direct oncogenic function of HIV in BL development. However, the molecular mechanisms underlying this HIV-associated malignancy are not well understood. This study explores the oncogenic potential of HIV-1 protein Tat in BL via its ability to manipulate the expression of c-MYC and activation-induced cytidine deaminase (AID), two key drivers of BL progression. Using dual-luciferase reporter assays, HIV-1 Tat was shown to enhance the activity of the cMYC promoter (-2324 bp - +537 bp), which corresponded with elevated c-MYC protein levels in BL cells (Ramos) expressing HIV-1 Tat. By generating sequential promoter deletions, the minimal promoter region mediating HIV-1 Tat induced activation was identified. Site-directed mutagenesis indicated that this response was mediated by AP-1 binding elements, and coimmunoprecipitation assays revealed that HIV-1 Tat and the AP-1 factor JunB interacted within the same complex. Chromatin immunoprecipitation assays confirmed that JunB bound the c-MYC promoter in vivo under the influence of HIV-1 Tat. The effect of HIV-1 Tat on the expression of the DNA editing enzyme AID was also investigated. Dual-luciferase assays revealed that HIV-1 Tat could enhance the activity of the three regulatory regions of the AICDA gene, namely R1, R2 and R4. This translated into elevated AID protein expression in Ramos cells expressing HIV-1 Tat, which was also reflected in an increase in genomic instability as shown by enhanced phosphorylated H2AX expression. Sequential promoter deletions of the R1 promoter did not lead to a loss in HIV-1 Tat-mediated activation, pointing to potential post-transcriptional regulation. Indeed, HIV-1 Tat was found to downregulate the expression of hsa-miRNA-181b-5p, a known repressor of the murine Aicda gene. Furthermore, using reporter assays, we show that an hsa-miRNA-181b5p mimic could repress AICDA via the full-length 3'UTR which contains three putative binding elements for the miRNA. To date, this study reveals that HIV-1 Tat induced c-MYC promoter activation is mediated by two AP-1 binding sites. HIV-1 Tat was shown to couple with JunB and bind to both AP-1 sites on the c-MYC promoter inducing promoter activation. Furthermore, this study reveals a novel mechanism of AID deregulation via HIV-1 Tat-mediated miRNA perturbation. Lastly, we show that HIV-1 Tat interferes with hsa-miRNA-181b-5p expression in B cells, alleviating AICDA 3'UTR repression.